VTA GABA Neurons at the Interface of Stress and Reward - Bouarab, Chloé; Thompson, Brittney; Polter, Abigail M. (Frontiers in Neural Circuits, 2019)
The ventral tegmental area (VTA) is best known for its robust dopaminergic projections to forebrain regions and their critical role in regulating reward, motivation, cognition, and aversion. However, the VTA is not only made of dopamine (DA) cells, as approximately 35% of cells in the VTA are GABA neurons. These neurons play a dual role, as VTA GABA neurons provide both local inhibition of VTA DA neurons and long-range inhibition of several distal brain regions. VTA GABA neurons have increasingly been recognized as potent mediators of reward and aversion in their own right, as well as potential targets for the treatment of addiction, depression, and other stress-linked disorders. In this review, we dissect the circuit architecture, physiology, and behavioral roles of VTA GABA neurons and suggest critical gaps to be addressed.